Exploring the Impacts of Board Flexibility on Non-Performing Assets and Firm Value in the Context of a Fastest Growing Economy - Islam, Md. Nazrul; Maniruzzaman, Md.; Hossain, Syed Zabid (International Journal of Economics and Financial Issues, 2024)
This paper plans to examine the effects of board extent on non-performing assets (NPA) and firm value measured as comprehensive financial performance (CFP) of banks in Bangladesh using data from 2016 to 2022. Using a sample of 210 firm-year observations, this paper reveals that NPA is significantly related to board size, which signals that a big board of directors (BODs) is linked with lowering the extent of NPA in the context of developing economies like Bangladesh. Besides, the affinity between board extent and firm value proxies as CFP is positive, but the result is not consequential. This research would be value additive to the literature because it examines the effects of board size on NPA and CFP, which is scanty in the corporate finance literature. Furthermore, this research finds no literature that applies CFP as the performance measure of banks, especially in Bangladesh.